Calibrating reconstruction radius in a multi single-element ultrasound-transducer-based photoacoustic computed tomography system - Kalva, Sandeep Kumar (2018)
In a circular scanning photoacoustic computed tomography (PAT/PACT) system, a single-element ultrasound transducer (SUT) (rotates in full 360° around the sample) or a full-ring array transducer is used to acquire the photoacoustic (PA) data from the target object. SUT takes several minutes to acquire the PA data, whereas the full-ring array transducer takes only few seconds. Hence, for real-time imaging, full-ring circular array transducers are preferred. However, these are custom built, very expensive, and not available readily on the market, whereas SUTs are cheap and easily available. Thus, PACT systems can be made cost effective by using SUTs. To improve the data acquisition speed, multiple SUTs can be employed at the same time. This will reduce the acquisition time by N-fold if N numbers of SUTs are used, each rotating 360/N degrees. Experimentally, all SUTs cannot be placed exactly at the same distance from the scanning center. Hence, the acquired PA data from each transducer need to be reconstructed with their corresponding radii in a delay-and-sum reconstruction algorithm. This requires the exact location of each SUT from the scanning center. Here, we propose a calibration method to find out the distance from the scanning center at which each SUT acquires the PA data. Three numerical phantoms were used to show the efficacy of the proposed method, and later it was validated with experimental data (point source phantom).